DIGITAL THREATS AND A HEALTHY FAMILY ENVIRONMENT: STEREOTYPE-FREE PARENTING IN THE MODERN ERA. (Universal International Scientific Journal, 2026)
This article analyzes the issues of maintaining a healthy family psychology and forming spiritual and moral immunity in young people in the face of the dangers of the digital world. The study examines the impact of gender stereotypes on child rearing and the modern transformation of social consciousness. The author reveals the integrated role of the family, religious organizations and state policy in the fight against information attacks. The article puts forward practical recommendations for stereotype-free upbringing methods and stabilization of family relations.
Keywords: digital world, family psychology, spiritual immunity, gender stereotypes, social institutions, information overload, education.